(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Problem behaviors are common among individuals with Major Neurocognitive Disorders (MND) and are associated with high levels of distress among caregivers and the decision about institutionalization. Despite its importance, the behavior-analytic literature regarding problem behavior with individuals with MND is less preeminent. The present study reviewed the literature in behavior analysis on assessing and managing problem behaviors among individuals with MND in the databases PsycInfo and Scielo. The search using the keywords resulted in 73 articles and 15 were considered for analysis. All articles were published in English. The publications targeted disruptive vocalizations, physical or verbal aggressions, wandering, among others. They present effective interventions to reduce problem behaviors. The feasibility of implementing interventions by caregivers and family members was also discussed.